Glucosylated Polymeric Micelles Actively Target a Breast Cancer Model. Issue 1 (13th May 2020) - Lecot, Nicole; Glisoni, Romina; Oddone, Natalia; Benech, Juan; Fernández, Marcelo; Gambini, Juan Pablo; Cabral, Pablo; Sosnik, Alejandro
Abstract: This work investigates the potential of glycosylation to actively target nanodrug delivery systems to adult solid tumors overexpressing glucose transporters. The highly hydrophobic fluorescent compound curcumin (CUR) is nanoencapsulated within polymeric micelles of pristine and glucosylated poly(ethylene oxide)‐poly(propylene oxide) block copolymers, and their interaction with breast cancer (BC) cells is investigated in vitro and in vivo. The aqueous solubility of CUR is increased more than 50 000‐fold and spherical nanoparticles display size in the 40 to 500 nm range, as determined by transmission electron microscopy and by dynamic light scattering, respectively. Uptake studies conducted in the BC cell line 4T1 in vitro demonstrate that glucosylation enhances nanoparticle internalization. Finally, the ability of unmodified and glucosylated polymeric micelles to accumulate in female BALB/c mice bearing 4T1‐induced tumors is compared by ex vivo bioimaging with auspicious results. Abstract : Glucosylation of polymeric micelles of poly(ethylene oxide)‐ b ‐poly(propylene oxide) block copolymers to actively target solid tumors overexpressing glucose transporters is explored by utilizing curcumin, a poorly water‐soluble and fluorescent molecule, as a drug model and tracer. Glucosylation enhances nanoparticle uptake by a breast cancer cell line in vitro and the selective intratumoral accumulation in BALB/c mice bearing 4T1‐induced tumors.